(untitled) (Scientific journal of the Fergana State University, 2025)
This article presents a study assessing the effectiveness of using the joint influence method to improve motor-coordination skills in school-age children (8-10 years old). As part of the experiment, a sample of schoolchildren was analyzed, and the results showed the potential of this method in increasing the level of motor activity in children. The findings represent an important contribution to the understanding of methods for optimizing the physical development of children and may be useful for the development of programs for the development of motor skills in the school environment. The experimental study was conducted on a group of schoolchildren, where specially developed methods and training programs were used. The results showed a significant increase in the level of motor activity in children, which indicates the potential of this method to effectively influence motor coordination skills. Such data may be useful in developing innovative programs and approaches to physical education for children in the school environment, promoting their healthy development and overall well-being.